The Effects of Reciting Al-Qur’an (Ruqyah Syar’iyyah) on Sleep Quality of Elderly People Living in a Nursing Home - Mardiyanti, Mardiyanti; Yuanita, Ita; Pratiwi, Sherly Mulya; Widada, Wahyudi (Universitas Darussalam Gontor, 2024)
Elderly are at risk of having poor sleep quality due to chronic illness, emotional distress, anxiety, environment, malnutrition and low physical activities. Evidence showed religious therapy effectively improve mental health, reduce anxiety and depression. However, the use of ruqyah syar’iyyah for managing sleep disturbance has not been studied well, therefore this research aimed to investigate the effectiveness of ruqyah therapy on sleep quality of elderly people. This study used Quasi Experimental with one group Pre-test Post-test design approach. Elderly in the nursing homes were selected based on their Pittsburgh Sleep Quality Index (PSQI) score. Seventeen elderly with PSQI> 5, Muslim and followed all the study program were participated in this study analysis. The intervention was done by reciting selected Surah in the Qur’an once a day for three nights. The post-test was held on the last day of data collection by measuring PSQI. The age of respondents range from 61-82 years old with the majority in the elderly age (60- to 74-year-old with 76,5%), most of the education level of the respondents were elementary school (64,7%). The PSQI mean score was 14,88 ± 2,09 (pre-test) vs 9.12 ± 1,6 (post-test) P-value<0.05. Ruqyah syar’iyyah improves the elderly quality of sleep by significantly reduces the PSQI score. Ruqyah therapy may help elderly managing psychological issues that interfere their sleep latency and sleep duration. However, the study does not differentiate the group base on the cause of poor sleep quality. Therefore, it is suggested to study the effect of ruqyah therapy based on the cause of poor sleep quality of the elderly. Nurses and other heathcare providers are suggested to use Ruqyah therapy for intervening poor sleep quality among elderly